7,8-dihydroxyflavone enhances long-term spatial memory and alters brain volume in wildtype mice - Rawlings-Mortimer, Florence; Lazari, Alberto; Tisca, Cristiana; Tachrount, Mohamed; Martins-Bach, Aurea B.; Miller, Karla L.; Lerch, Jason P.; Johansen-Berg, Heidi (Frontiers in Systems Neuroscience, 2023)
Introduction: 7,8-dihydroxyflavone (7,8-DHF) is a low molecular weight compound that can cross the blood brain barrier and has been implicated in numerous functions and behaviours. It is thought to have neuroprotective capability and has been shown to alleviate symptoms in a wide range of diseases. Methods: 7,8-DHF was administered systemically to wildtype mice during Morris water maze training. Long-term spatial memory was assessed 28 days later. Ex-vivo T2-weighted (T2w) imaging was undertaken on a subset of these mice to assess brain-wide changes in volume. Results: We found that systemic 7,8-DHF administration during the training period enhanced spatial memory 28 days later. Volumetric changes were observed in numerous brain regions associated with a broad range of functions including cognition, sensory, and motor processing. Discussion: Our findings give the first whole brain overview of long-term anatomical changes following 7,8-DHF administration providing valuable information for assessing and understanding the widespread effects this drug has been shown to have in behaviour and disease.